Análise da inserção do enfermeiro nos processos de educação permanente na saúde da família no município de São Carlos/SP - Moçambique, Maria Diamantina Francisco Fernandes (2012)
The processes of Continuing Education in Health (EPS) nurses inclusion in the Family Health Strategy (FHS) are studied aiming to identify the perceptions of nurses on continuing education as a way of work s reorganization. This is a qualitative research in the sphere of meanings constructed based on the theoretical work process. The data collection was made up by semi-structured interview after the informed consent of a total 15 nurses working in the FHS in São Carlos / SP, and has analyzed the empirical data using the technique of content analysis based on the theoretical results in three thematic 1) Continuing Education in Health versus Labour Process, 2) Facilities and Difficulties regarding EPS and 3) Actions undertaken in relation to the EPS. The results analysis showed that although nurses have the comprehensionthat EPS work process occur or should occur concurrently; this is not an easy task to put on a day-to-day work. The role of the nurse as a facilitator of educational processes still not solidifiedand the use of collective spaces for integration of actors and the expansion of autonomy. We also emphasize the importance of training professionals for the practice of EPS, considering the different concepts brought by the participants. The nurses maintain the notion of priority to management issues beside of the expense of neglecting the educational needs EPS as detector and form of solving the problems of practice. Another factor that can be seen is the lack of user involvement when it comes to EPS. Thus it is concluded the need for further research on the EPS and consequences for the quality of care users towards transformation of healthcare practices.